Bullying experiences among university students: an observation / Aqilfikri Irfan Taqiuddin Tiew …[et al.] - Taqiuddin Tiew, Aqilfikri Irfan; Mohd Nawi, Nur Alia Tasnim; Hasan, Nur Syafika; Abdullah, Nurul Mahirah; Rosmi, Siti Nur Suzainie (Universiti Teknologi MARA (UiTM), 2020)
Bullying is a term often described as aggressive intentional actions or behaviours performed by a group or individual repeatedly from time to time against victims who are unable to defend themselves easily or himself (Olweus, 1994). There are many types of bullying that can be experienced by university students, some can be seen clearly while others can be more subtle. The types that can be categorized as bullying are physical bullying, verbal bullying, mental bullying and cyberbullying. Studies from within and outside the country show that direct bullying such as physical bullying and verbal bullying are most often reported to occur in universities. Often the symptoms of bullying start with verbal bullying done through ridicule, name calling and ridicule. As for physical type bullying, it involves acts such as beating, biting, kicking, pinching, kicking and slapping. Uncontrolled physical bullying will result in the death of the victim of bullying. The category of indirect bullying that is sometimes difficult to detect is mental bullying or also known as psychological bullying. This type of bullying is a form of psychological attack, namely through acts such as spreading slander, boycotting, isolation and flying letters. In addition, gestures such as squinting, cynical smiles and squealing also fall under the category of psychological bullying. Often, psychologically bullied students experience stress and loss of self-esteem as a result of spreading stories and gossip about themselves in public. Cyber bullying is the abuse of technological devices such as mobile phones and computers. Examples of cyber bullying include the spread of defamation through electronic mail and social media, text messages of threatening or abusive language, and the dissemination of videos of requests to bring down the dignity of the victim.